2010
DOI: 10.1016/j.jsps.2009.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Leptin levels in relation to marital status and neuroendocrine function in Iraqi females with polycystic ovary syndrome

Abstract: The present study was designed to evaluate the relationship between serum leptin levels and the hormones related to fertility in Iraqi females with polycystic ovary syndrome (PCOS) and marital status. This study was conducted during the period from July to December 2007. Twenty-four women (12 married and 12 unmarried) with PCOS and not maintained on any type of therapy were included in the study. Twelve healthy and normal ovulatory women with an age range matched with that of PCOS women were included. After an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…According to our results unmarried polycystic ovarian syndrome patients were more acceptable to experience polycystic ovarian syndrome when compared to married patients. It is also an agreement with earlier finding of [18] who pointed out polycystic ovarian syndrome is more common among unmarried females in comparison with married females. This could lead to decrease serum Leptin altitude in class of polycystic ovarian syndrome female compared to non-polycystic ovarian syndrome women [19].…”
Section: Discussionsupporting
confidence: 93%
“…According to our results unmarried polycystic ovarian syndrome patients were more acceptable to experience polycystic ovarian syndrome when compared to married patients. It is also an agreement with earlier finding of [18] who pointed out polycystic ovarian syndrome is more common among unmarried females in comparison with married females. This could lead to decrease serum Leptin altitude in class of polycystic ovarian syndrome female compared to non-polycystic ovarian syndrome women [19].…”
Section: Discussionsupporting
confidence: 93%
“…Several Iraqi studies showed the risk of PCOS in women in various areas, Sharqui and colleagues found that free testosterone was positive marker to enhance diagnosis of PCOS (13). Khalaf found that leptin level was associated with endocrinological belongs to fertility (14). Maluki found that PCOS is common factor in women to prevent acne vulgaris (15).…”
Section: Discussionmentioning
confidence: 99%